Preparation of Carbon Adsorbent by Utilizing Waste Materials for LPG Gas Storage - Herawan, Safarudin Gazali; Mohamad, Imran Syakir; Mohd Husin, Mohd Haizal; Yusof, Ahmad Anas; Mat Tokit, Ernie (2004)
Coconut shell and oil palm shell are an agricultural waste material found abundantly in Malaysia. Since the characteristics of coconut shell and oil palm shell were found suitable for preparing activated carbon, these materials also have the potential to be prepared into other useful and valuable products. This research, the concern is to make use of coconut shell or oil palm shell which it mixed with plastic bag to prepare the carbon adsorbent, which applied for LPG storage. This sample was prepared at a laboratory scale fixed-bed reactor, which is blanketed by a vertical furnace where pyrolysis took place. Nitrogen gas was used to obtain an inert atmosphere in the reactor. A suction blower was used to remove volatile matter as well as other gases during carbonization process. The samples were prepared in the different peak temperature and amount of the plastic bag which it mixed with them. This research work will attempt to find a suitable solution to solve the environmental problems by utilizing the waste materials and to look into the industrial aspect of adsorption process for gas storage.